Estimating wastewater dilution using chemical markers and incomplete flow measurements: Application to normalisation of SARS-CoV-2 measurements - Owen D. Jones; Amy J. Baldwin; Isabelle Durance; William B. Perry; Andrew Weightman (Journal of Water Process Engineering, 2026)

Neurobehavioral and metabolic consequences of embryonic triphenyl phosphate exposure across the lifespan in zebrafish - Andrew B. Hawkey; Perry Piatos; Zade R. Holloway; Dilanaz Unal; Jonna Boyda; Richard T. Di Giulio; Edward D. Levin (Neurotoxicology and Teratology, 2026)

Efferent projections of topographically distinct relaxin family peptide receptor-3 (RXFP3) lateral hypothalamus/zona incerta cells - Brandon K. Richards; Alexander I. J. Kilby; Jennifer L. Cornish; Jee Hyun Kim; Andrew J. Lawrence; Christina J. Perry (Brain Structure and Function, 2026)
Relaxin family peptide receptor-3 (RXFP3) is a ligand-activated G-protein coupled receptor and the cognate receptor for the conserved neuropeptide relaxin-3. We recently demonstrated that chemogenetically activating an RXFP3-expressing population in the lateral hypothalamus and zona incerta (LH/ZI RXFP3 ) induced escape-like jumping behaviour following fear conditioning, but only in a subset of mice. Given the diverse hodology of the LH and ZI, we hypothesised that LH/ZI RXFP3 cells may consist of discrete subpopulations with unique connectivity patterns that govern different aspects of defensive behaviour. To explore this possibility, we unilaterally injected small volumes of a Cre-dependent anterograde viral tracer into four distinct sites of the LH/ZI in RXFP3-Cre mice and analysed their brain-wide efferent connectivity patterns. Each injection site group produced unique projection patterns, particularly to nuclei involved in threat and defensive behaviour. Of note were strong projections from the rostral ZI and anterior LH to the lateral habenula, and projections from the intermediate and caudal ZI to the ventrolateral periaqueductal gray. By combining retrograde tracing and RNAscope fluorescent in situ hybridisation, we identified that most LH/ZI RXFP3 projections to the lateral habenula arose from a subset of vGlut2-expressing lateral hypothalamus neurons, while most projections to the ventrolateral periaqueductal gray arose from a subset of GAD1-expressing zona incerta neurons. Taken together, our results strongly suggest that LH/ZI RXFP3 cells exhibit distinct efferent projection patterns throughout the brain depending on their topographical location within these nuclei, likely reflecting the functional diversity of these neurons.

Prioritising actions over space and time in multi-habitat ecological restoration: Insights from indicator species in coastal seascapes - Ben L. Gilby; Andrew D. Olds; Michael Sievers; Maria L. Vozzo; Brittany B. Elliott; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Ashley J. Rummell; Christopher J. Henderson (Landscape and Urban Planning, 2026)

Comparative efficacy of electrokinetic and static leaching for selective metal recovery and nutrient release from porphyry Cu tailings - Yujie Yan; Gawen R.T. Jenkin; Andrew P. Abbott; Alexandria Tanciongco; Carlo A. Arcilla; Cris Reven L. Gibaga; Daniel J. Smith; Djoan Kate Tungpalan; Jonathan E. Chambers; John Henry C. Gervasio; James Symons; Justine Perry T. Domingo; et al. (Chemical Engineering Journal, 2026)

Towards a global barcode reference library for subterranean fauna - Michelle T. Guzik; Jake Thornhill; Mieke van der Heyde; Danielle N. Stringer; Nicole E. White; Mattia Saccò; Perry G. Beasley-Hall; Paul Nevill; Rachael A. King; Steven J.B. Cooper; Andrew D. Austin (Science of The Total Environment, 2026)

Genome-resolved metagenomics uncovers antimicrobial resistance gene carriers in hospital and municipal wastewater environments - Reshma Silvester; Gordon Webster; William B. Perry; Kata Farkas; Laura Rushton; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; Davey L. Jones (Science of The Total Environment, 2025)

The Cost of Antivenom: A Cost Minimization Study using the North American Snakebite Registry - Benjamin Herzel; Neev Batavia; Paul Gavaza; Tammy Phan; Emmelyn Samones; Anne-Michelle Ruha; Jakub Furmaga; Christopher Hoyte; Brian J. Wolk; Peter Akpunonu; Adam Algren; Alexandra Amaducci; et al. (Journal of Medical Toxicology, 2025)
Envenomation is a global health issue, with over 9,000 encounters managed in the United States yearly. The introduction of immunoglobulin fragment antivenom has reduced the risk of hypersensitivity. This study compares treatment costs of crotaline envenomation using the Fab and F(ab’) 2 antivenoms as reported to the North American Snakebite Registry (NASBR), a nationwide surveillance tool. Methods This was a retrospective analysis of NASBR data between 2018 and 2020. The following data points were assessed: patient demographics (age, gender, race), snake species, type of antivenom used, and treatment costs. Unit costs were estimated based on United States Centers for Medicare and Medicaid Services data. Average (mean) per patient costs from the payer perspective were calculated by multiplying resources by the unit costs. Sensitivity analyses were performed regarding cost variance and snake species. All costs reported in this study are in U.S. dollars. Results The average total cost of treatment was $31,343 per person, with medications contributing 72% of the total. Average total cost among patients who received Fab treatments was $33,347 per person compared to $19,747 among patients who received F(ab’) 2 . Antivenom costs accounted for 75% of the total cost in the Fab group and 42% in the F(ab’) 2 group. F(ab’) 2 required more vials than Fab (median 18 versus 10). Non-antivenom costs such as hospitalizations were higher in the F(ab’) 2 group. Using average sale prices increased average total cost to $52,572; Fab remained more expensive. Conclusion Antivenom is the primary cost driver in snakebite treatment in North America. Treatment with F(ab’) 2 resulted in lower overall costs, driven by lower cost of antivenom. F(ab’) 2 did not significantly lower overall resource use except for blood product administration.

Seasonal monitoring of dissolved and particulate algal biotoxins in the northern Salish Sea using high performance liquid chromatography and tandem mass spectrometry - Andrew R.S. Ross; Béatrice Ip; Mackenzie Mueller; Blair Surridge; Harry Hartmann; Navinder Hundal; Nathan Matthews; Hayleigh Shannon; Melissa Hennekes; Akash Sastri; R. Ian Perry (Harmful Algae, 2025)

Systemic toxicity after rattlesnake envenomation in patients using angiotensin converting enzyme inhibitors: A North American Snakebite Registry study - A.M. Ruha; M.B. Spyres; R. Culbreth; B. Wolk; C. Hoyte; S. Campleman; Peter Akpunonu; Adam Algren; Alexandra Amaducci; Sukhshant Atti; Connie Aubin; Kevin Baumgartner; et al. (Toxicon, 2025)

Metagenomics unveils the role of hospitals and wastewater treatment plants on the environmental burden of antibiotic resistance genes and opportunistic pathogens - Reshma Silvester; William B. Perry; Gordon Webster; Laura Rushton; Amy Baldwin; Daniel A. Pass; Nathaniel Healey; Kata Farkas; Noel Craine; Gareth Cross; Peter Kille; Andrew J. Weightman; et al. (Science of The Total Environment, 2025)

Assessing greenspace and cardiovascular health through deep-learning analysis of street-view imagery in a cohort of US children - Li Yi; Sheryl Rifas-Shiman; Marcia Pescador Jimenez; Pi-I Debby Lin; Esra Suel; Perry Hystad; Andrew Larkin; Steve Hankey; Wenwen Zhang; Jochem Klompmaker; Emily Oken; Marie-France Hivert; et al. (Environmental Research, 2025)

Coral carbonate production across depth: homogenisation after bleaching? - Sivajyodee Sannassy Pilly; Ronan C. Roche; Ines D. Lange; Chris T. Perry; Andrew O. M. Mogg; Kathryn Dawson; John R. Turner (Coral Reefs, 2024)
Recurrent climate-driven warming events, which can induce severe coral bleaching and mortality on tropical reefs, are predicted to cause homogenisation of coral communities and loss of ecosystem functions in shallow reef systems (< 30 m). However, data documenting the variation in coral carbonate production across depth are limited. Here we explore differences in coral cover, community composition, coral colony size structure and carbonate production rates between two depths (10 m and 17.5 m) across four atolls in the remote Chagos Archipelago. We show higher coral carbonate production rates at 10 m (4.82 ± 0.27 G, where G = kg CaCO 3 m −2 yr −1 ) compared to sites at 17.5 m (3.1 ± 0.18 G). The main carbonate producers at 10 m consisted of fast-growing branching and tabular corals (mainly Acroporids) and massive corals (mainly Porites ), with high abundances of medium- and large-sized colonies. In contrast, coral carbonate production at 17.5 m was driven by slow-growing encrusting and foliose morphotypes and small colony sizes. Utilising a dataset following 6–7 years of recovery after the 2015–2017 bleaching event, our results show that depth-homogenisation of coral communities was temporary and carbonate production rates at 10 m depth recovered quicker at 3 of 4 studied atolls. The exception is Great Chagos Bank where slower recovery of branching and tabular corals at 10 m has led to a longer-lasting depth-homogenisation of carbonate production rates. The latter example cautions that more frequent bleaching events may drive increasing homogenisation of carbonate production rates across depth gradients, with implications for vital reef geo-ecological functions.

Influence of commercial inactivated or modified-live virus vaccination at time of AI on corpus luteum development and function in beef cattle - K.M. Epperson; J.J.J. Rich; S. Menegatti Zoca; L.K. Quail; T.N. Andrews; A.C. Kline; F.J. White; R.F. Daly; R.A. Cushman; A.P. Snider; G.A. Perry (Animal Reproduction Science, 2024)

National-scale antimicrobial resistance surveillance in wastewater: A comparative analysis of HT qPCR and metagenomic approaches - Margaret E. Knight; Gordon Webster; William B. Perry; Amy Baldwin; Laura Rushton; Daniel A. Pass; Gareth Cross; Isabelle Durance; Windi Muziasari; Peter Kille; Kata Farkas; Andrew J. Weightman; et al. (Water Research, 2024)

Quantifying Environmental and Spatial Patterns of Fish on Log Snags to Optimise Resnagging in Coastal Seascapes - Lucy A. Goodridge Gaines; Jesse D. Mosman; Christopher J. Henderson; Andrew D. Olds; Hannah J. Perry; Ben L. Gilby (Estuaries and Coasts, 2024)
Long-term declines in coastal water quality and sedimentation can affect the restoration success of ecosystems such as seagrass and shellfish reefs. Resnagging coastal seascapes offers a potential alternative restoration method that is not reliant on abiotic conditions and which may enhance degraded landscapes for fish and fisheries. While common in freshwater ecosystems, such interventions are unusual for coastal seascapes despite log snags supporting significant benefits for coastal fish. In this study, we identify the spatial (e.g. seascape connectivity), habitat condition (e.g. log snag complexity and food availability) and water quality variables that best explain variation in fish assemblages on log snags to help prioritise the placement and design of resnagging efforts in estuaries. We surveyed fish assemblages on log snags using underwater videography at 363 sites across 13 estuaries in southeast Queensland, Australia, over 3 years. Sites less than 10,000 m from the estuary mouth, more than 2500 m from urban structures and located in water depths of < 3 m harboured more diverse fish assemblages. Sites less than 10,000 m from the estuary mouth with lower (< 25%) algae cover harboured greater total fish abundance and harvested fish abundance. Similar trends were found for the abundance of individuals from key functional groups, although these trends were mediated by other seascape contexts (e.g. the area of natural habitat) and water quality variables (e.g. chlorophyll-a concentration and dissolved oxygen saturation). Our results indicate that log snag placement in estuaries for benefits to fish and fisheries can be maximised if sites are planned strategically.

Examining the stability of viral RNA and DNA in wastewater: Effects of storage time, temperature, and freeze-thaw cycles - Rachel C. Williams; William B. Perry; Kathryn Lambert-Slosarska; Ben Futcher; Cameron Pellett; India Richardson-O'Neill; Steve Paterson; Jasmine M.S. Grimsley; Matthew J. Wade; Andrew J. Weightman; Kata Farkas; Davey L. Jones (Water Research, 2024)

Flood effects on estuarine fish are mediated by seascape composition and context - Christopher J. Henderson; Andrew D. Olds; Lucy A. Goodridge Gaines; Jesse D. Mosman; Hannah J. Perry; Hayden P. Borland; Ben L. Gilby (Marine Biology, 2024)
Estuaries are crucial feeding, nursery and resting sites for fish but can also be subject to the impacts of severe flooding. The environmental features of estuaries can mediate how they respond to these impacts. For example, the size, configuration, and context of estuarine habitats across seascapes affects the value of patches for fish, and so fish assemblages at sites with a greater habitat extent or closer to the mouth of an estuary may rebound more quickly from flooding. We investigated how a once in 100-year flood event affected fish assemblages at approximately 600 sites across 13 estuaries and six estuarine habitats (bare sediments, log snags, mangrove forests, rocky structures, saltmarsh and seagrass meadows) in southeast Queensland, Australia, and determined whether flood impacts were mediated by the position of sites within the broader estuarine seascape. Sites were surveyed annually in 2020/2021 (pre-flood) and 2022 (6 months post-flood) using underwater videography. Flooding modified the structure of the fish community and reduced the abundance of fish targeted by local fisheries in all six habitats. Crucially, flood effects on fish were greater at sites near more expansive urbanisation in some ecosystems, but lower at sites nearer to the estuary mouth. Maximising the extent of natural habitats across estuaries can mediate the effects of floods and should be priorities for restoration and management plans seeking to maintain biodiversity and fisheries productivity in the face of increasing climate-related disturbances.

Phylogenomic analyses of multidrug resistant Corynebacterium striatum strains isolated from patients in a tertiary care hospital in the UK - Vartul Sangal; Emma C. L. Marrs; Andrew Nelson; John D. Perry (European Journal of Clinical Microbiology & Infectious Diseases, 2024)
Corynebacterium striatum is an emerging nosocomial pathogen. This is the first report showing the presence of three distinct multidrug resistant lineages of C. striatum among patients in a UK hospital. The presence of ErmX, Tet(W), Bla and AmpC proteins, and mutations in gyrA gene are associated with the resistance to clindamycin, doxycycline, penicillin and moxifloxacin, respectively. These strains are equipped with several corynebacterial virulence genes including two SpaDEF-type and a novel pilus gene cluster, which needs further molecular characterisation. This study highlights a need of developing an active surveillance strategy for routine monitoring and preventing potential cross-transmission among susceptible patients.

Cross-continental comparative experiences of wastewater surveillance and a vision for the 21st century - William Bernard Perry; Mariana Cardoso Chrispim; Mikaela Renata Funada Barbosa; Marcelo de Souza Lauretto; Maria Tereza Pepe Razzolini; Adelaide Cassia Nardocci; Owen Jones; Davey L. Jones; Andrew Weightman; Maria Inês Zanoli Sato; Cassiana Montagner; Isabelle Durance (Science of The Total Environment, 2024)

A new multispectral index for canopy nitrogen concentration applicable across growth stages in ryegrass and barley - Manish Kumar Patel; Dongryeol Ryu; Andrew W. Western; Glenn J. Fitzgerald; Eileen M. Perry; Helen Suter; Iain M. Young (Precision Agriculture, 2024)
Accurately monitoring Canopy Nitrogen Concentration (CNC) is a prerequisite for precision nitrogen (N) fertiliser management at the farm scale with carbon and N budgeting across the landscape and ecosystems. While many spectral indices have been proposed for CNC monitoring, their applicability and accuracy are often adversely affected by confounding factors such as aboveground biomass (AGB), crop type, growth stages, and environmental conditions, limiting their broader application and adoption; with AGB being one of the most dominant signals and confounding factors at canopy scale. The confounding effect can become more challenging as AGB is also physiologically linked with CNC across the growth stages. Additionally, the interplay between index form, selection of optimal wavebands and their bandwidths remains poorly understood for CNC index design. This study proposes robust and cost-effective 2- and 4-waveband multispectral (MS) CNC indices applicable across a wide range of crop conditions. We collected 449 canopy reflectance spectra (400–980 nm) together with corresponding CNC and AGB measurements across four growth stages of ryegrass (winter and summer), and five growth stages of barley (winter-spring) in Victoria, Australia, in 2018 and 2019. All possible waveband (400–980 nm) combinations revealed that the best combination varied between seasons and crop types. However, the visible spectrum, particularly the blue region, presented high and consistent performance. Bandwidths of 10–40 nm outperformed either very narrow (2 nm) or very broad bandwidths (80 nm). The newly developed 2-waveband index (416 and 442 nm with 10-nm bandwidth; R 2 = 0.75 and NRMSE = 0.2) and 4-waveband index (512, 440, 414 and 588 nm with 40-nm bandwidth; R 2 = 0.81 and NRMSE = 0.17) exhibited the best performance, while validation with an independent dataset (from a different growing period to those used in the model development) obtained NRMSE values of 0.25 and 0.24, respectively. The 4-waveband index provides enhanced performance and permits use of broader bandwidths than its 2-waveband counterpart.

Evaluation of two beef cow fixed-time AI protocols that utilize presynchronization - Jaclyn N. Ketchum; Lacey K. Quail; Kaitlin M. Epperson; Chloey P. Guy; Jerica J.J. Rich; Saulo Menegatti Zoca; Adalaide C. Kline; Taylor N. Andrews; Julie A. Walker; Pedro Levy Piza Fontes; Sandy K. Johnson; Megan P.T. Owen; et al. (Theriogenology, 2024)

Global sensitivity analysis of APSIM-wheat yield predictions to model parameters and inputs - Shirui Hao; Dongryeol Ryu; Andrew W Western; Eileen Perry; Heye Bogena; Harrie Jan Hendricks Franssen (Ecological Modelling, 2024)

Domoic acid in Canadian Pacific waters, from 2016 to 2021, and relationships with physical and chemical conditions - R. Ian Perry; Nina Nemcek; Melissa Hennekes; Akash Sastri; Andrew R.S. Ross; Hayleigh Shannon; Ryan B. Shartau (Harmful Algae, 2023)

Simulating the migration dynamics of juvenile salmonids through rivers and estuaries using a hydrodynamically driven enhanced particle tracking model - Vamsi Krishna Sridharan; Doug Jackson; Andrew M. Hein; Russell W. Perry; Adam C. Pope; Noble Hendrix; Eric M. Danner; Steven T. Lindley (Ecological Modelling, 2023)

Influence of preovulatory estradiol treatment on the maintenance of pregnancy in beef cattle receiving in vivo produced embryos - J.N. Ketchum; G.A. Perry; L.K. Quail; K.M. Epperson; M.A. Ogg; A.L. Zezeski; J.J.J. Rich; S. Menegatti Zoca; A.C. Kline; T.N. Andrews; M.S. Ortega; M.F. Smith; et al. (Animal Reproduction Science, 2023)

Drivers of Ecological Condition Identify Bright Spots and Sites for Management Across Coastal Seascapes - Ben L. Gilby; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Jesse D. Mosman; Andrew D. Olds; Hannah J. Perry (Estuaries and Coasts, 2023)
Disentangling natural and anthropogenic effects on ecosystem condition can uncover bright spots in urban landscapes that are performing above expectations and so are potential sites for conservation or benchmarking, as well as sites performing below expectations that should be the focus of management. In this study, we tested for correlations between metrics indexing ecological condition (focusing on habitat-forming species) and a suite of spatial and environmental variables at 373 sites across four ecosystems (mangroves, seagrass, saltmarsh and rocky outcrops) and 13 estuaries in southeast Queensland, Australia. Ten condition metrics across the four ecosystems correlated with variables indexing the seascape context of sites, with condition metrics typically higher at sites more connected to natural features including the estuary mouth and mangroves. Urbanisation affected only two metrics, with rocky outcrop oyster cover being 75% lower at sites near extensive urbanisation and algae cover being highest at sites with intermediate urbanisation. We identified patterns in at least two variables from each ecosystem, meaning that decisions need to be made regarding optimal ecosystem states. Overall, management sites were more common than bright spots, with 50% more management sites in mangroves, 42.8% more in seagrasses, 38.5% more in saltmarshes and no bright spots in rocky outcrops (however, 10.3% of rocky outcrop sites were bright spots under an alternate ecosystem state model). We found that patterns in habitat condition across coastal seascapes can be predicted using spatial modelling approaches, and that these models can be readily used to prioritise management actions across the entire regions.

Retrieving canopy nitrogen concentration and aboveground biomass with deep learning for ryegrass and barley: Comparing models and determining waveband contribution - Manish Kumar Patel; José Padarian; Andrew W. Western; Glenn J. Fitzgerald; Alex B. McBratney; Eileen M. Perry; Helen Suter; Dongryeol Ryu (Field Crops Research, 2023)

Identifying optimal values of coastal habitat condition for management and restoration - Hannah J. Perry; Lucy A. Goodridge Gaines; Hayden P. Borland; Christopher J. Henderson; Andrew D. Olds; Jesse D. Mosman; Ben L. Gilby (Estuarine, Coastal and Shelf Science, 2023)

The American Lobster Settlement Index: History, lessons, and future of a long-term, transboundary monitoring collaborative - M. Conor McManus; Damian C. Brady; Curtis Brown; Joshua T. Carloni; Melanie Giffin; Andrew G. Goode; Kristyn Kleman; Peter Lawton; Arnault Le Bris; Scott Olszewski; Derek N. Perry; Rémy Rochette; et al. (Frontiers in Marine Science, 2023)
Understanding the processes that influence recruitment variability in marine populations has been a long-standing challenge for resource management. Quantifying abundance at early life stages for marine fish and invertebrates with complex life histories can be difficult and require unconventional sampling approaches. However, the benefit of developing appropriate tools to sample early life stages is that, together with associated demographic and environmental information, the data can provide insights into the causes and consequences of recruitment variability, allowing prediction of older life stage abundance. Before the 1980s, the earliest benthic life stages of the American lobster ( Homarus americanus ) eluded quantitative field surveys. With the development of diver-based and vessel-deployed sampling methods over the past three decades, the American Lobster Settlement Index (ALSI) program has expanded into a regional, transboundary commitment to better understand lobster settlement processes and forecast future fishery trends for what has become the most valuable single-species fishery in North America. In this context, “settlement” is a shorthand for the annual recruitment of young-of-year lobster to coastal nurseries, as postlarvae settle to the seabed at the end of larval development. Here, we review the development and products of the ALSI program, first outlining the goals, methods, and data products of the program. We then highlight how the program has advanced the scientific knowledge on pre- and post-settlement processes that influence the fate of a cohort from egg hatch to harvest, which provides insight into the spawner-recruit relationship. Lastly, we provide guidance for future research recommendations building on the ALSI science to-date, some major elements of the program that have allowed for its success, and considerations for maintaining the ALSI program. By highlighting the uniqueness and contributions of the ALSI program, we hope it serves as a model for other scientists, managers, and industry collaborators aiming to understand recruitment processes for species over a broad geographic area.

A Case Study of Large Floodplain River Restoration: Two Decades of Monitoring the Merwin Preserve and Lessons Learned through Water Level Fluctuations and Uncontrolled Reconnection to a Large River - Levi E. Solomon; Andrew F. Casper; Kristopher A. Maxson; James T. Lamer; Trent W. Ford; K. Douglass Blodgett; Tharran Hobson; Denim Perry; Nathan T. Grider; Rob B. Hilsabeck; Thad R. Cook; Kevin S. Irons; et al. (Wetlands, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Invasion of Siberian Elm (Ulmus pumila) Along the South Platte River: the Roles of Seed Source, Human Influence, and River Geomorphology - Lindsay V. Reynolds; Laura G. Perry; Patrick B. Shafroth; Gabrielle Katz; Andrew Norton (Wetlands, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

The scope and severity of white‐nose syndrome on hibernating bats in North America - Tina L. Cheng; Jonathan D. Reichard; Jeremy T. H. Coleman; Theodore J. Weller; Wayne E. Thogmartin; Brian E. Reichert; Alyssa B. Bennett; Hugh G. Broders; Joshua Campbell; Katherine Etchison; Daniel J. Feller; Richard Geboy; et al. (Conservation Biology, 2021)
Assessing the scope and severity of threats is necessary for evaluating impacts on populations to inform conservation planning. Quantitative threat assessment often requires monitoring programs that provide reliable data over relevant spatial and temporal scales, yet such programs can be difficult to justify until there is an apparent stressor. Leveraging efforts of wildlife management agencies to record winter counts of hibernating bats, we collated data for 5 species from over 200 sites across 27 U.S. states and 2 Canadian provinces from 1995 to 2018 to determine the impact of white‐nose syndrome (WNS), a deadly disease of hibernating bats. We estimated declines of winter counts of bat colonies at sites where the invasive fungus that causes WNS ( Pseudogymnoascus destructans ) had been detected to assess the threat impact of WNS. Three species undergoing species status assessment by the U.S. Fish and Wildlife Service ( Myotis septentrionalis , Myotis lucifugus , and Perimyotis subflavus ) declined by more than 90%, which warrants classifying the severity of the WNS threat as extreme based on criteria used by NatureServe. The scope of the WNS threat as defined by NatureServe criteria was large (36% of Myotis lucifugus range) to pervasive (79% of Myotis septentrionalis range) for these species. Declines for 2 other species ( Myotis sodalis and Eptesicus fuscus ) were less severe but still qualified as moderate to serious based on NatureServe criteria. Data‐sharing across jurisdictions provided a comprehensive evaluation of scope and severity of the threat of WNS and indicated regional differences that can inform response efforts at international, national, and state or provincial jurisdictions. We assessed the threat impact of an emerging infectious disease by uniting monitoring efforts across jurisdictional boundaries and demonstrated the importance of coordinated monitoring programs, such as the North American Bat Monitoring Program (NABat), for data‐driven conservation assessments and planning.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Larval cross‐shore transport estimated from internal waves with a background flow: The effects of larval vertical position and depth regulation - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2021)
Cross‐shore velocities in the coastal ocean typically vary with depth. The direction and magnitude of transport experienced by meroplanktonic larvae will therefore be influenced by their vertical position. To quantify how swimming behavior and vertical position in internal waves influence larval cross‐shore transport in the shallow (~ 20 m), stratified coastal waters off Southern California, we deployed swarms of novel, subsurface larval mimics, the Mini‐Autonomous Underwater Explorers (M‐AUEs). The M‐AUEs were programmed to maintain a specified depth, and were deployed near a mooring. Transport of the M‐AUEs was predominantly onshore, with average velocities up to 14 cm s −1 . To put the M‐AUE deployments into a broader context, we simulated > 500 individual high‐frequency internal waves observed at the mooring over a 14‐d deployment; in each internal wave, we released both depth‐keeping and passive virtual larvae every meter in the vertical. After the waves' passage, depth‐keeping virtual larvae were usually found closer to shore than passive larvae released at the same depth. Near the top of the water column (3–5‐m depth), ~ 20% of internal waves enhanced onshore transport of depth‐keeping virtual larvae by ≥ 50 m, whereas only 1% of waves gave similar enhancements to passive larvae. Our observations and simulations showed that depth‐keeping behavior in high‐frequency internal waves resulted in enhanced onshore transport at the top of the water column, and reduced offshore dispersal at the bottom, compared to being passive. Thus, even weak depth‐keeping may allow larvae to reach nearshore adult habitats more reliably than drifting passively.

Responses of ichthyoplankton assemblages to the recent marine heatwave and previous climate fluctuations in several Northeast Pacific marine ecosystems - Jens M. Nielsen; Lauren A. Rogers; Richard D. Brodeur; Andrew R. Thompson; Toby D. Auth; Alison L. Deary; Janet T. Duffy‐Anderson; Moira Galbraith; J. Anthony Koslow; R. Ian Perry (Global Change Biology, 2021)
The effects of climate warming on ecosystem dynamics are widespread throughout the world's oceans. In the Northeast Pacific, large‐scale climate patterns such as the El Niño/Southern Oscillation and Pacific Decadal Oscillation, and recently unprecedented warm ocean conditions from 2014 to 2016, referred to as a marine heatwave (MHW), resulted in large‐scale ecosystem changes. Larval fishes quickly respond to environmental variability and are sensitive indicators of ecosystem change. Categorizing ichthyoplankton dynamics across marine ecosystem in the Northeast Pacific can help elucidate the magnitude of assemblage shifts, and whether responses are synchronous or alternatively governed by local responses to regional oceanographic conditions. We analyzed time‐series data of ichthyoplankton abundances from four ecoregions in the Northeast Pacific ranging from subarctic to subtropical: the Gulf of Alaska (1981–2017), British Columbia (2001–2017), Oregon (1998–2017), and the southern California Current (1981–2017). We assessed the impact of the recent (2014–2016) MHW and how ichthyoplankton assemblages responded to past major climate perturbations since 1981 in these ecosystems. Our results indicate that the MHW caused widespread changes in the ichthyoplankton fauna along the coast of the Northeast Pacific Ocean, but impacts differed between marine ecosystems. For example, abundances for most dominant taxa were at all‐time lows since the beginning of sampling in the Gulf of Alaska and British Columbia, while in Oregon and the southern California Current species richness increased as did abundances of species associated with warmer waters. Lastly, species associated with cold waters also increased in abundances close to shore in southern California during the MHW, a pattern that was distinctly different from previous El Niño events. We also found several large‐scale, synchronized ichthyoplankton assemblage composition shifts during past major climate events. Current climate projections suggest that MHWs will become more intense and thus our findings can help project future changes in larval dynamics, allowing for improved ecosystem management decisions.

St. Helena: An Important Reproductive Habitat for Whale Sharks (Rhincodon typus) in the Central South Atlantic - Cameron T. Perry; Elizabeth Clingham; D. Harry Webb; Rafael de la Parra; Simon J. Pierce; Annalea Beard; LeeAnn Henry; Beth Taylor; Kenickie Andrews; Rhys Hobbs; Gonzalo Araujo; Alistair D. M. Dove (Frontiers in Marine Science, 2020)

A review of a decade of lessons from one of the world’s largest MPAs: conservation gains and key challenges - Graeme C. Hays; Heather J. Koldewey; Samantha Andrzejaczek; Martin J. Attrill; Shanta Barley; Daniel T. I. Bayley; Cassandra E. Benkwitt; Barbara Block; Robert J. Schallert; Aaron B. Carlisle; Pete Carr; Taylor K. Chapple; et al. (Marine Biology, 2020)

The role of psychology in determining human–predator conflict across southern Kenya - Laura R. Perry; Tom P. Moorhouse; Andrew J. Loveridge; David W. Macdonald (Conservation Biology, 2020)
Conflict between people and carnivores can lead to the widespread killing of predators in retaliation for livestock loss and is a major threat to predator populations. In Kenya, a large, rural, pastoralist population comes into regular conflict with predators, which persist across southern Kenya. We explored the social and psychological backdrop to livestock management practices in this area in a process designed to be easy to use and suitable for use across large areas for the study of conflict and transboundary implementation of wildlife conflict reduction measures, focusing on community involvement and needs. We carried out fully structured interviews of livestock managers with a survey tool that examined how social and psychological factors may influence livestock management behavior. We compared survey responses on 3 sites across the study area, resulting in 723 usable responses. Efficacy of individuals’ livestock management varied between and within communities. This variation was partially explained by normative and control beliefs regarding livestock management. Individual livestock managers’ self‐reported management issues were often an accurate reflection of their practical management difficulties. Psychological norms, control beliefs, and attitudes differed among sites, and these differences partially explained patterns associated with conflict (i.e., variation in livestock management behavior). Thus, we conclude that a one‐size‐fits‐all approach to improving livestock management and reducing human–predator conflict is not suitable.

A novel cross‐shore transport mechanism revealed by subsurface, robotic larval mimics: Internal wave deformation of the background velocity field - Jessica C. Garwood; Andrew J. Lucas; Perry Naughton; Matthew H. Alford; Paul L. D. Roberts; Jules S. Jaffe; Laura deGelleke; Peter J. S. Franks (Limnology and Oceanography, 2020)
Coastal physical processes are essential for the cross‐shore transport of meroplanktonic larvae to their benthic adult habitats. To investigate these processes, we released a swarm of novel, trackable, subsurface vehicles, the Mini‐Autonomous Underwater Explorers (M‐AUEs), which we programmed to mimic larval depth‐keeping behavior. The M‐AUE swarm measured a sudden net onshore transport of 30–70 m over 15–20 min, which we investigated in detail. Here, we describe a novel transport mechanism of depth‐keeping plankton revealed by these observations. In situ measurements and models showed that, as a weakly nonlinear internal wave propagated through the swarm, it deformed surface‐intensified, along‐isopycnal background velocities downward, accelerating depth‐keeping organisms onshore. These higher velocities increased both the depth‐keepers' residence time in the wave and total cross‐shore displacement, leading to wave‐induced transports twice those of fully Lagrangian organisms and four times those associated with the unperturbed background currents. Our analyses also show that integrating velocity time series from virtual larvae or mimics moving with the flow yields both larger and more accurate transport estimates than integrating velocity time series obtained at a point (Eulerian). The increased cross‐shore transport of organisms capable of vertical swimming in this wave/background‐current system is mathematically analogous to the increase in onshore transport associated with horizontal swimming in highly nonlinear internal waves. However, the mechanism described here requires much weaker swimming speeds (mm s −1 vs. cm s −1 ) to achieve significant onshore transports, and meroplanktonic larvae only need to orient themselves vertically, not horizontally.

Steps to Develop Early Warning Systems and Future Scenarios of Storm Wave-Driven Flooding Along Coral Reef-Lined Coasts - Gundula Winter; Curt Storlazzi; Sean Vitousek; Ap van Dongeren; Robert McCall; Ron Hoeke; William Skirving; John Marra; Johan Reyns; Jerome Aucan; Matthew Widlansky; Janet Becker; et al. (Frontiers in Marine Science, 2020)

Enhancing gardens as habitats for soil-surface-active invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Temporal relationship between the Lassen volcanic center and mafic regional volcanism - Aurelie Germa; Chris Perry; Xavier Quidelleur; Andrew Calvert; Michael Clynne; Charles B. Connor; Laura J. Connor; Rocco Malservisi; Sylvain Charbonnier (Bulletin of Volcanology, 2019)

Novel ecological and climatic conditions drive rapid adaptation in invasive Florida Burmese pythons - Daren C. Card; Blair W. Perry; Richard H. Adams; Drew R. Schield; Acacia S. Young; Audra L. Andrew; Tereza Jezkova; Giulia I.M. Pasquesi; Nicole R. Hales; Matthew R. Walsh; Michael R. Rochford; Frank J. Mazzotti; et al. (Molecular Ecology, 2018)
Invasive species provide powerful in situ experimental systems for studying evolution in response to selective pressures in novel habitats. While research has shown that phenotypic evolution can occur rapidly in nature, few examples exist of genomewide adaptation on short “ecological” timescales. Burmese pythons ( Python molurus bivittatus ) have become a successful and impactful invasive species in Florida over the last 30 years despite major freeze events that caused high python mortality. We sampled Florida Burmese pythons before and after a major freeze event in 2010 and found evidence for directional selection in genomic regions enriched for genes associated with thermosensation, behaviour and physiology. Several of these genes are linked to regenerative organ growth, an adaptive response that modulates organ size and function with feeding and fasting in pythons. Independent histological and functional genomic data sets provide additional layers of support for a contemporary shift in invasive Burmese python physiology. In the Florida population, a shift towards maintaining an active digestive system may be driven by the fitness benefits of maintaining higher metabolic rates and body temperature during freeze events. Our results suggest that a synergistic interaction between ecological and climatic selection pressures has driven adaptation in Florida Burmese pythons, demonstrating the often‐overlooked potential of rapid adaptation to influence the success of invasive species.

A multidisciplinary-based conceptual model of a fractured sedimentary bedrock aquitard: improved prediction of aquitard integrity - Anthony C. Runkel; Robert G. Tipping; Jessica R. Meyer; Julia R. Steenberg; Andrew J. Retzler; Beth L. Parker; Jeff A. Green; John D. Barry; Perry M. Jones (Hydrogeology Journal, 2018)

Front Cover - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)

Global importance of large‐diameter trees - James A. Lutz; Tucker J. Furniss; Daniel J. Johnson; Stuart J. Davies; David Allen; Alfonso Alonso; Kristina J. Anderson‐Teixeira; Ana Andrade; Jennifer Baltzer; Kendall M. L. Becker; Erika M. Blomdahl; Norman A. Bourg; et al. (Global Ecology and Biogeography, 2018)
Aim To examine the contribution of large‐diameter trees to biomass, stand structure, and species richness across forest biomes. Location Global. Time period Early 21st century. Major taxa studied Woody plants. Methods We examined the contribution of large trees to forest density, richness and biomass using a global network of 48 large (from 2 to 60 ha) forest plots representing 5,601,473 stems across 9,298 species and 210 plant families. This contribution was assessed using three metrics: the largest 1% of trees ≥ 1 cm diameter at breast height (DBH), all trees ≥ 60 cm DBH, and those rank‐ordered largest trees that cumulatively comprise 50% of forest biomass. Results Averaged across these 48 forest plots, the largest 1% of trees ≥ 1 cm DBH comprised 50% of aboveground live biomass, with hectare‐scale standard deviation of 26%. Trees ≥ 60 cm DBH comprised 41% of aboveground live tree biomass. The size of the largest trees correlated with total forest biomass ( r 2 = .62, p r 2 = .45, p r 2 = .33, p r 2 = .17, p = .002). The concentration of biomass in the largest 1% of trees declined with increasing absolute latitude ( r 2 = .46, p r 2 = .31, p r 2 = .26, p Main conclusions Because large‐diameter trees constitute roughly half of the mature forest biomass worldwide, their dynamics and sensitivities to environmental change represent potentially large controls on global forest carbon cycling. We recommend managing forests for conservation of existing large‐diameter trees or those that can soon reach large diameters as a simple way to conserve and potentially enhance ecosystem services.

New steps for treating alcohol use disorder - Erin J. Campbell; Andrew J. Lawrence; Christina J. Perry (Psychopharmacology, 2018)

Investigating the candidacy of the serotype specific rhamnan polysaccharide based glycoconjugates to prevent disease caused by the dental pathogen Streptococcus mutans - Frank St. Michael; Qingling Yang; Chantelle Cairns; Evgeny Vinogradov; Perry Fleming; Alexander C. Hayes; Annie Aubry; Andrew D. Cox (Glycoconjugate Journal, 2018)

Enhancing gardens as habitats for plant-associated invertebrates: should we plant native or exotic species? - Andrew Salisbury; Sarah Al-Beidh; James Armitage; Stephanie Bird; Helen Bostock; Anna Platoni; Mark Tatchell; Ken Thompson; Joe Perry (Biodiversity and Conservation, 2017)

Size‐based fruit selection by a keystone avian frugivore and effects on seed viability - Andrew Paul McKenzie Pegman; George L. W. Perry; Mick N. Clout (New Zealand Journal of Botany, 2017)
The non‐random selection of fruits by frugivores can affect plant demography by changing the probability of seedling recruitment. We investigated whether the New Zealand pigeon ( Hemiphaga novaeseelandiae ) exhibits size‐based preference of fruit in two indigenous tree species, Vitex lucens and Prumnopitys ferruginea , that have large fleshy diaspores containing single seeds. We also assessed if there was an advantage for seeds that were actively dispersed since birds may select fruits that have viable seeds (although the cue for such selection remains unclear) and whether a combined scarification–deinhibition advantage was conferred on germination due to seed passage through the gut. Using seed length as a proxy for fruit size, we compared the length of passively dispersed fruits in traps with the estimated fruit length of actively dispersed seeds in six trees of each species across three areas in one fruiting season. For both species, actively dispersed seeds were significantly longer than seeds from passively dispersed fruit, suggesting frugivore preference for larger fruit. Seeds from passively dispersed P. ferruginea fruit had significantly higher viability than actively dispersed seeds and there was no measurable scarification–deinhibition effect. For V. lucens , there was no significant difference in viability between actively and passively dispersed seeds and there was a total lack of seed germination in our trial. Our results show a significant preference by H. novaeseelandiae for larger fruit in both tree species, which was possibly associated with annual fruit production since P. ferruginea trees that had more fruit produced larger fruit on average. That H. novaeseelandiae selected longer fruit in our study is consistent with the prediction that birds will prefer larger fruit when beak gape limitation is absent. However, active dispersal of larger seeds may not always be advantageous since passively dispersed intact fruit germinated equally well and may even have had a viability advantage.

Warming and provenance limit tree recruitment across and beyond the elevation range of subalpine forest - Lara M. Kueppers; Erin Conlisk; Cristina Castanha; Andrew B. Moyes; Matthew J. Germino; Perry de Valpine; Margaret S. Torn; Jeffry B. Mitton (Global Change Biology, 2017)
Climate niche models project that subalpine forest ranges will extend upslope with climate warming. These projections assume that the climate suitable for adult trees will be adequate for forest regeneration, ignoring climate requirements for seedling recruitment, a potential demographic bottleneck. Moreover, local genetic adaptation is expected to facilitate range expansion, with tree populations at the upper forest edge providing the seed best adapted to the alpine. Here, we test these expectations using a novel combination of common gardens, seeded with two widely distributed subalpine conifers, and climate manipulations replicated at three elevations. Infrared heaters raised temperatures in heated plots, but raised temperatures more in the forest than at or above treeline because strong winds at high elevation reduced heating efficiency. Watering increased season‐average soil moisture similarly across sites. Contrary to expectations, warming reduced Engelmann spruce recruitment at and above treeline, as well as in the forest. Warming reduced limber pine first‐year recruitment in the forest, but had no net effect on fourth‐year recruitment at any site. Watering during the snow‐free season alleviated some negative effects of warming, indicating that warming exacerbated water limitations. Contrary to expectations of local adaptation, low‐elevation seeds of both species initially recruited more strongly than high‐elevation seeds across the elevation gradient, although the low‐provenance advantage diminished by the fourth year for Engelmann spruce, likely due to small sample sizes. High‐ and low‐elevation provenances responded similarly to warming across sites for Engelmann spruce, but differently for limber pine. In the context of increasing tree mortality, lower recruitment at all elevations with warming, combined with lower quality, high‐provenance seed being most available for colonizing the alpine, portends range contraction for Engelmann spruce. The lower sensitivity of limber pine to warming indicates a potential for this species to become more important in subalpine forest communities in the coming centuries.

Hybrid plants preserve unique genetic variation in the St Helena endemic trees Commidendrum rotundifolium DC Roxb. and C. spurium (G.Forst.) DC - Alan Gray; Annika Perry; Stephen Cavers; Antonia Eastwood; Michelle Biermann; Andrew Darlow; Vanessa Thomas; Phil Lambdon (Conservation Genetics, 2017)

CTFS ‐Forest GEO : a worldwide network monitoring forests in an era of global change - Kristina J. Anderson‐Teixeira; Stuart J. Davies; Amy C. Bennett; Erika B. Gonzalez‐Akre; Helene C. Muller‐Landau; S. Joseph Wright; Kamariah Abu Salim; Angélica M. Almeyda Zambrano; Alfonso Alonso; Jennifer L. Baltzer; Yves Basset; Norman A. Bourg; et al. (Global Change Biology, 2015)
Global change is impacting forests worldwide, threatening biodiversity and ecosystem services including climate regulation. Understanding how forests respond is critical to forest conservation and climate protection. This review describes an international network of 59 long‐term forest dynamics research sites ( CTFS ‐Forest GEO ) useful for characterizing forest responses to global change. Within very large plots (median size 25 ha), all stems ≥1 cm diameter are identified to species, mapped, and regularly recensused according to standardized protocols. CTFS ‐Forest GEO spans 25°S–61°N latitude, is generally representative of the range of bioclimatic, edaphic, and topographic conditions experienced by forests worldwide, and is the only forest monitoring network that applies a standardized protocol to each of the world's major forest biomes. Supplementary standardized measurements at subsets of the sites provide additional information on plants, animals, and ecosystem and environmental variables. CTFS ‐Forest GEO sites are experiencing multifaceted anthropogenic global change pressures including warming (average 0.61 °C), changes in precipitation (up to ±30% change), atmospheric deposition of nitrogen and sulfur compounds (up to 3.8 g N m −2 yr −1 and 3.1 g S m −2 yr −1 ), and forest fragmentation in the surrounding landscape (up to 88% reduced tree cover within 5 km). The broad suite of measurements made at CTFS ‐Forest GEO sites makes it possible to investigate the complex ways in which global change is impacting forest dynamics. Ongoing research across the CTFS ‐Forest GEO network is yielding insights into how and why the forests are changing, and continued monitoring will provide vital contributions to understanding worldwide forest diversity and dynamics in an era of global change.

Determining the influence of environmental and patient specific factors on the polymicrobial communities of the cystic fibrosis airway - Andrew Nelson; Audrey Perry; John D. Perry; Stephen J. Bourke; Stephen P. Cummings; Anthony De Soyza (Antonie van Leeuwenhoek, 2013)

The safety of studies with intravenous Δ9-tetrahydrocannabinol in humans, with case histories - Michelle Carbuto; R. Andrew Sewell; Ashley Williams; Kim Forselius-Bielen; Gabriel Braley; Jacqueline Elander; Brian Pittman; Ashley Schnakenberg; Savita Bhakta; Edward Perry; Mohini Ranganathan; Deepak Cyril D’Souza (Psychopharmacology, 2012)

Mercury in breeding saltmarsh sparrows (Ammodramus caudacutus caudacutus) - Oksana P. Lane; Kathleen M. O’Brien; David C. Evers; Thomas P. Hodgman; Andrew Major; Nancy Pau; Mark J. Ducey; Robert Taylor; Deborah Perry (Ecotoxicology, 2011)

Chronic cocaine exposure induces putamen glutamate and glutamine metabolite abnormalities in squirrel monkeys - Xiaoxu Liu; J. Eric Jensen; Timothy E. Gillis; Chun S. Zuo; Andrew P. Prescot; Melanie Brimson; Kenroy Cayetano; Perry F. Renshaw; Marc J. Kaufman (Psychopharmacology, 2011)

GBR 12909 administration as a mouse model of bipolar disorder mania: mimicking quantitative assessment of manic behavior - Jared W. Young; Andrew K. L. Goey; Arpi Minassian; William Perry; Martin P. Paulus; Mark A. Geyer (Psychopharmacology, 2010)

Vulnerability of national economies to the impacts of climate change on fisheries - Edward H. Allison; Allison L. Perry; Marie‐Caroline Badjeck; W. Neil Adger; Katrina Brown; Declan Conway; Ashley S. Halls; Graham M. Pilling; John D. Reynolds; Neil L. Andrew; Nicholas K. Dulvy (Fish and Fisheries, 2009)
Anthropogenic global warming has significantly influenced physical and biological processes at global and regional scales. The observed and anticipated changes in global climate present significant opportunities and challenges for societies and economies. We compare the vulnerability of 132 national economies to potential climate change impacts on their capture fisheries using an indicator‐based approach. Countries in Central and Western Africa (e.g. Malawi, Guinea, Senegal, and Uganda), Peru and Colombia in north‐western South America, and four tropical Asian countries (Bangladesh, Cambodia, Pakistan, and Yemen) were identified as most vulnerable. This vulnerability was due to the combined effect of predicted warming, the relative importance of fisheries to national economies and diets, and limited societal capacity to adapt to potential impacts and opportunities. Many vulnerable countries were also among the world’s least developed countries whose inhabitants are among the world’s poorest and twice as reliant on fish, which provides 27% of dietary protein compared to 13% in less vulnerable countries. These countries also produce 20% of the world’s fish exports and are in greatest need of adaptation planning to maintain or enhance the contribution that fisheries can make to poverty reduction. Although the precise impacts and direction of climate‐driven change for particular fish stocks and fisheries are uncertain, our analysis suggests they are likely to lead to either increased economic hardship or missed opportunities for development in countries that depend upon fisheries but lack the capacity to adapt.

A therapeutic dose of zolpidem reduces thalamic GABA in healthy volunteers: a proton MRS study at 4 T - Stephanie C. Licata; J. Eric Jensen; David M. Penetar; Andrew P. Prescot; Scott E. Lukas; Perry F. Renshaw (Psychopharmacology, 2009)

DNA-Protein Cross-Links in Erythrocytes of Freshwater Fish Exposed to Hexavalent Chromium or Divalent Nickel - Jim R. Kuykendall; Kyle L. Miller; Kristen M. Mellinger; Andrew J. Cain; Michael W. Perry; Michael Bradley; Eric J. Jarvi; Dennis J. Paustenbach (Archives of Environmental Contamination and Toxicology, 2009)

An extract of Salvia (sage) with anticholinesterase properties improves memory and attention in healthy older volunteers - Andrew B. Scholey; Nicola T. J. Tildesley; Clive G. Ballard; Keith A. Wesnes; Andrea Tasker; Elaine K. Perry; David O. Kennedy (Psychopharmacology, 2008)

An intronic sequence mutated in flexed-tail mice regulates splicing of Smad5 - Shailaja Hegde; Laurie E. Lenox; Andrew Lariviere; Prashanth Porayette; John M. Perry; Michele Yon; Robert F. Paulson (Mammalian Genome, 2007)

Escalation of i.v. cocaine self-administration and reinstatement of cocaine-seeking behavior in rats bred for high and low saccharin intake - Jennifer L. Perry; Andrew D. Morgan; Justin J. Anker; Nancy K. Dess; Marilyn E. Carroll (Psychopharmacology, 2006)

Forest Structure and Fire Susceptibility in Volcanic Landscapes of the Eastern High Cascades, Oregon - DAVID A. PERRY; HUANG JING; ANDREW YOUNGBLOOD; DOUG R. OETTER (Conservation Biology, 2004)
Multidimensional forest health initiatives—those designed to restore and protect forest integrity in the large sense—require, among other things, a better understanding of the relationship between the structure of forests and (1) their susceptibility to wildfires outside the range of natural variability and (2) the level of treatment (if any) required to lower susceptibility into an acceptable range. Within the ponderosa pine zone (Pinus ponderosa Dougl. ex Laws.) on the eastern slopes of Oregon's Cascade Range, an average of 86% of trees >5 cm in diameter at breast height (dbh) were less than 101 years old, the density of young trees correlating negatively with the density of old trees (>150 yrs). Species composition differed significantly between age classes: 72% of trees older than 150 years were ponderosa pine, whereas 83% of trees younger than 101 years were either grand fir ( Abies grandis [Dougl.] Lindl.) or lodgepole pine ( Pinus contorta Dougl. ex). Loud Crown bulk density calculated to reflect the multiple canopy layer structure of these stands (CBDm) averaged 0.049 kg/m 3 , compared to 0.093 kg/m 3 using the standard approach ( p 2 = 0.92), implying that over certain ranges small changes in basal area result in relatively large changes in susceptibility (assuming that changes in basal area are due to addition or removal of smaller trees). Landsat thematic mapper correlates reasonably well with CBDm ( r 2 = 0.80) and may provide a tool for rapid risk assessment.

Assessment of prey overlap between a native ( Polistes humilis ) and an introduced ( Vespula germanica ) social wasp using morphology and phylogenetic analyses of 16S rDNA - Marta L. Kasper; Andrew F. Reeson; Steven J. B. Cooper; Kym D. Perry; Andrew D. Austin (Molecular Ecology, 2004)
In newly invaded communities, interspecific competition is thought to play an important role in determining the success of the invader and its impact on the native community. In southern Australia, the native Polistes humilis was the predominant social wasp prior to the arrival of the exotic Vespula germanica (Hymenoptera: Vespidae) . Both species forage for similar resources (water, pulp, carbohydrate and protein prey), and concerns have arisen about potential competition between them. The aim of this study was to identify the protein foods that these wasps feed on. As many prey items are masticated by these wasps to the degree that they cannot be identified using conventional means, morphological identification was complemented by sequencing fragments of the mitochondrial 16S rRNA gene. GenBank searches using blast and phylogenetic analyses were used to identify prey items to at least order level. The results were used to construct complete prey inventories for the two species. These indicate that while P. humilis is restricted to feeding on lepidopteran larvae, V. germanica collects a variety of prey of invertebrate and vertebrate origin. Calculated values of prey overlap between the two species are used to discuss the implications of V. germanica impacting on P. humilis. Results obtained are compared to those gained by solely ‘conventional’ methods, and the advantages of using DNA‐based taxonomy in ecological studies are emphasized.

DIETS OF FIN, SEI, AND SPERM WHALES IN BRITISH COLUMBIA: AN ANALYSIS OF COMMERCIAL WHALING RECORDS, 1963–1967 - Rowenna D. Flinn; Andrew W. Trites; Edward J. Gregr; R. Ian Perry (Marine Mammal Science, 2002)
A bstract Diets of fin ( Balaenoptera physalus ), sei ( Balaenoptera borealis ), and sperm whales ( Physeter macrocephalus ) were estimated from the stomach contents of individuals killed along the British Columbia coast from 1963 to 1967. The dominant prey types of fin whales were euphausiids, with minor contributions from copepods and fish. Sei whale stomachs contained primarily copepods in three years, whereas euphausiids or a variety of fish dominated the diet in the other two years. Sperm whales consumed primarily North Pacific giant squid ( Moroteuthis robusta ), but secondary prey differed between males and females. Female sperm whales frequently consumed ragfish ( Icosteus spp.) and other fish, whereas the male diet also contained rockfish ( Sebastes spp.). The high abundance of euphausiids along the British Columbia coast likely contributed to the presence of a summer resident population of fin whales. The high abundance of large copepods farther north probably influenced the migration of sei whales through the offshore waters of British Columbia. Sperm whale stomach contents differed by sex reflecting location and possibly breeding behaviors.

Temporary alteration of local social structure in a threatened population of Cuban iguanas ( Cyclura nubila ) - Allison Alberts; Jeffrey Lemm; Andrew Perry; Lisa Morici; John Phillips (Behavioral Ecology and Sociobiology, 2002)

The effects of 10 days of spaceflight on the shuttle Endeavour on predominantly fast-twitch muscles in the rat - William J. Kraemer; Robert S. Staron; Scott E. Gordon; Jeff S. Volek; L. Perry Koziris; Noel D. Duncan; Bradley C. Nindl; Ana L. Gómez; James O. Marx; Andrew C. Fry; Jerry D. Murray (Histochemistry and Cell Biology, 2000)

Population biology of a failed invasion: Paleolimnology of Daphnia exilis in upstate New York - Nelson G. Hairston; Linda J. Perry; Andrew J. Bohonak; Meghan Q. Fellows; Colleen M. Kearns; Daniel R. Engstrom (Limnology and Oceanography, 1999)
Viable diapausing eggs of Daphnia exilis , a species within the Daphnia similis species complex, occur in sediments of Onondaga Lake, New York. The discovery of this species, which otherwise occurs exclusively in temporary saline ponds in southwestern North America, represents a range extension of 1,000 km. 210 Pb‐dating of the sediments containing diapausing eggs indicates that D. exilis was present in Onondaga Lake between the mid‐1920s and the early 1980s. The species' introduction, successful colonization, and subsequent disappearance from the water column correspond temporally with distinct events in the history of industrial activity along the shores of the lake and with the paleoecological record of this activity deposited in Onondaga Lake sediments. Only the most recently deposited diapausing eggs (late 1970s to early 1980s) hatch during laboratory incubation; older eggs may not be viable because of toxic concentrations of mercury pollution in older sediments. The D. exilis eggs that have hatched have had strikingly low genetic (allozyme) variation in comparison with the variation documented for populations in the southwestern United States by Hebert and Finston (1993). Exploration of various invasion scenarios through simulated introduction of genotypes from the southwestern United States suggests that a single genotype established the D. exilis population in Onondaga Lake. These observations document the ecological and microevolutionary patterns associated with an invasion by an exotic crustacean that currently persists only in the sediment egg bank.